Transmission and distribution electrical engineering - Bayliss, C. R. (Colin R.)
Most books on transmission and distribution electrical engineering are student texts that focus on theory, brief overviews, or specialised monographs. Colin Bayliss and Brian Hardy have produced a unique and comprehensive handbook aimed squarely at practising engineers and planners involved in all aspects of getting electricity from the power plant to the user via the power grid. The scope of this book embraces power systems, substations, cabling, switchgear, power systems protection, overhead lines, project management, planning, regulations, and more... The third edition has been fully updated throughout in line with current IEC and European standards, an approach which has resulted in a thoroughly rewritten chapter on earthing and bonding and significant revisions to the chapters on EMC, insulation coordination and overhead line design. There is increased emphasis on reliability concepts and greatly expanded treatment of the subject of power quality.. The resulting book is an essential guide and a hard-working reference for all engineers, technicians, managers and planners involved in the electricity supply industry, and related areas such as generation, and industrial electricity usage. 1.A reference handbook written by engineers for engineers 2.Unrivalled in its scope, covering systems, substations, cabling, switchgear, power systems protection, overhead lines, project management, planning, regulations, and more... 3.The third edition includes expanded sections on power quality, a thoroughly updated section on earthing and bonding, and coverage of the integration embedded generation and renewables in modern power systems.